The Difference in Pain Levels Between Benson Relaxation Intervention and Guided Imagery in Post-Operative Caesarean Section Patients - Fina Salsabila Muqorrobin; imam - subekti; Tri Nataliswati (Jurnal Keperawatan Terapan, 2025)
The purpose of this study was to determine the difference in pain levels by giving benson relaxation and guided imagery to post-SC patients in the Mojolangu Health Center area in Malang City in 2024. This research design used quasi experiment two-group pre-test post-test design. The sampling technique in this study was accidental sampling with a sample of 28 people divided into 2 groups, namely the Benson relaxation group and the guided imagery group. The independent variable is Benson relaxation technique and guided imagery and the dependent variable is pain level. Measurement of pre and post pain scale using numeric rating scale. The bivariate data analysis test used the Wilcoxon test and Mann-whitney test to determine the difference in the decrease in pre and post pain levels and the difference in post pain in 2 groups. The results showed that the pain level of the Benson relaxation group before being given relaxation was on average moderate and after being given relaxation the average pain level became painless. The pain level of the guided imagery group before the intervention averaged moderate pain and after the intervention became mild pain. The statistical test results of the p-value value of 0.000 (<Alpha 0.05), so it can be concluded that there is a difference in pain levels after being given an intervention in the Benson relaxation group and the guided imagery group in post-SC mothers in the Mojolangu Malang City Health Center working area in 2024. It is expected that health center staff can apply these two methods to post-SC mothers to reduce their pain levels.